2000
DOI: 10.1159/000056820
|View full text |Cite
|
Sign up to set email alerts
|

The species and chromosomal distribution of the centromeric α-satellite I sequence from sheep in the tribe Caprini and other Bovidae

Abstract: The evolution of chromosomes in species in the family Bovidae includes fusion and fission of chromosome arms (giving different numbers of acrocentric and metacentric chromosomes with a relatively conserved total number of arms) and evolution in both DNA sequence and copy number of the pericentromeric α-satellite I repetitive DNA sequence. Here, a probe representing the sheep α-satellite I sequence was isolated and hybridized to genomic DNA digests and metaphase chromosomes from various Bovidae species. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 17 publications
6
44
0
Order By: Relevance
“…For in situ hybridization on chromosomes and extended chromatin fibres, a satellite I sheep clone pOaKB9 (Chaves et al 2000a(Chaves et al , 2003b) and a satellite I cattle clone, (pBtKB5, GenBank AJ293510, Chaves et al 2000bChaves et al , 2003a labelled Table 1. In situ hybridization patterns with probes sheep satellite I DNA (pOaKB9) and cattle satellite I DNA (pBtKB5) in all chromosome preparations of the 15 Bovidae species analysed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For in situ hybridization on chromosomes and extended chromatin fibres, a satellite I sheep clone pOaKB9 (Chaves et al 2000a(Chaves et al , 2003b) and a satellite I cattle clone, (pBtKB5, GenBank AJ293510, Chaves et al 2000bChaves et al , 2003a labelled Table 1. In situ hybridization patterns with probes sheep satellite I DNA (pOaKB9) and cattle satellite I DNA (pBtKB5) in all chromosome preparations of the 15 Bovidae species analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Both Modi et al (1993Modi et al ( , 1996 and Chaves et al (2000a) observed different satellite DNA in situ hybridization patterns within a small number of tribes in the Bovidae family, and we considered that the sequences had potential as phylogenetic markers to increase the resolution of the evolutionary tree at the base of the Artiodactyla (Chaves et al 2000a). Here we aimed to analyse the presence and distribution of satellites to address evolutionary and phylogenetic questions with respect to the X chromosome (and its primitive state), karyotype, species and tribal evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquity and persis-tence of heterochromatin in these genomes suggest that this distinctive genomic component has an adaptive value, be-sides being considered a genomic compartment carrying out important functions with an unconventional structural and functional basis (Dimitri et al 2004). Among other repetitive sequences, this genomic fraction comprises satellite DNAs that usually reside in the centromeric regions of chromo-somes (Chaves et al 2000). Identification of CH and its size differences is made feasible by the simple but extremely useful C-banding technique.…”
Section: Introductionmentioning
confidence: 99%
“…1). The sheep satellite I DNA (the 1.714 family) has a repeat unit of 820 bp and, as the bovine satellites, constitutes the centromeric heterochromatin of all autosomes, but not of the sex chromosomes (Buckland, 1983;Burkin et al, 1996;Chaves et al, 2000;Chaves et al, 2005). However, the amount and organization of satellite I DNA differ among the autosomes, with a lower amount at the centromeres of the biarmed chromosomes 1, 2, and 3, particularly of chromosome 1 (Burkin et al, 1996;D'Aiuto et al, 1997).…”
Section: Cetartiodactylamentioning
confidence: 99%